Lethal toxicity of monocrotophos on the juveniles of Anabas testudineus (Bloch) and Etroplus maculatus (Bloch) - Anna Mercy, T V; Kurup, B Madhusoodana; Nair, J R; Sulekha, B T (Indian Journal of Fisheries, 2011)
Studies on the lethal toxicity of the pesticide on two species of fish namely Anabas testudineus and Etroplus maculatus inhabiting the Kuttanad areas revealed that the 48 h LC50 values of monocrotophos on the juveniles of the respective fishes were 102.59 and 3.36 ppm. Anabas was found to be more tolerant than Etroplus. Etroplus maculatus is a sensitive fish that can be used for toxicity monitoring in natural waters.